The dynamics of motivated perception: effects of control and status on the perception of ambivalent stimuli - Voß, Andreas; Schwieren, Christiane (Cognition & emotion, 2015)
Previous studies on attentional biases often show contradictory results. This suggests that important moderating variables have been neglected so far. We suggest that (1) control over potential consequences and (2) satisfaction with the current status are important factors that need to be considered. We explored the influence of these variables using a colour classification task, where colours are associated with financial gains and losses. Data were analysed with hierarchical logistic regression models and with stochastic diffusion models. The latter approach has the special advantage that it allows separating perceptual and judgemental biases. Results show an overall positive judgemental bias. In the absence of control, this positivity bias increases with the amount of money that has been gained, whereas the opposite pattern is present when dangers can be controlled. In the second experiment, no general feedback was given, which led to an increasing negativity bias. Results are discussed within an action theoretic framework.
First published online 5 December 2014
Gesehen am 25.06.2020